Juridical Review Regarding Maladministration of Crude Palm Oil (CPO) Exports in Indonesia - Faisal Santiago (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper tracks the maladministration of CPO exports by conducting a judicial review of CPO export policies by the Ministry of Trade of the Republic of Indonesia. This study uses a normative legal analysis with a field research approach. The results of the judicial review of this study are that the policy of temporarily stopping the export of Crude Palm Oil by the government is entirely appropriate, considering that previously there was maladministration carried out by individuals at the Ministry of Trade involving palm oil entrepreneurs in three companies, the occurrence of export permits has entered the criteria for maladministration because the three companies The CPO manager does not have an export permit which causes state economic losses due to rising cooking oil prices due to excess CPO being exported.